GLOBAL BRANDS IN SCIENTIFIC RESEARCH: TRENDS OF THE LAST DECADE - Shtovba, Olena; Shtovba, Serhiy (Scientific Works of Vinnytsia National Technical University, 2019)
The dynamics of the research support by the global brands and the dynamics of the global brands usage in the research are analyzed over the last decode. The analysis was carried out according to the scientometic approach with the Scopus base data. The support was assessed by the number of publications in which the global brand is mentioned in the section on the research funding. The usage was assessed by the number publications in which the global brand is mentioned in the presentation part of the article, i. e., in the title, key words or in the abstract. The research was carried out for the global brands from the list of top-100 the most expensive brands according to the data of Interbrand company. Twenty-two brands with the unique names were selected: Google, Microsoft, Coca-Cola, Samsung, Toyota, Facebook, IBM, Cisco, Louis Vuitton, Pepsi, Budweiser, Ebay, Hyundai, Accenture, Volkswagen, Adidas, Morgan Stanley, Huawei, Harley-Davidson, Netflix, Johnnie Walker and Lenovo. The selected brands represent ten sectors of the economy. Greater part of brands – 16 out of 22 belong to the cluster with the equivalent levels of support and usage. The most generous and popular are the brands Google, Microsoft, IBM, Samsung, Volkswagen, Toyota and Facebook. All of them are connected with the information systems and services or with automobile construction. All the brands with high and average levels of support are characterized by the considerable growth of the number of the supported articles over the past two years. Among the analyzed brands the scientists use Google in most cases. During 2017 the number of the articles, where Google is mentioned in the presentation part, exceeded 5500. Facebook, Microsoft and IBM are also among the leaders. All the four brands from the high group as well as Samsung and Netflix from the average group demonstrate stable growth of their usage in the scientific research during the past several years.